BIMBINGAN TEKNIS PEMODELAN DISPERSI POLUTAN EMISI UDARA MENGGUNAKAN AERMOD BAGI DINAS LINGKUNGAN HIDUP PROVINSI JAWA TIMUR - Jawwad, Muhammad Abdus Salam; Murti, Restu Hikmah Ayu (Environmental Engineering Journal of Community Dedication, 2025)
This community service activity aims to enhance the technical capacity of local government officers in air pollutant dispersion modeling. The training was held on February 5–6, 2025, at the Environmental Agency of East Java Province, involving participants from the Sub-division of Air Pollution Control, within the Division of Pollution and Environmental Damage Control. The program was designed as a technical guidance on the use of the AERMOD software, developed by the U.S. EPA. The training materials covered fundamental concepts of atmospheric dispersion, required input data, model configuration, and output interpretation. The implementation method included theoretical sessions and hands-on tutorials using case studies based on real data. The results indicate a significant improvement in participants’ understanding and technical ability to apply AERMOD in assessing pollutant dispersion. This activity is expected to support evidence-based policymaking in air pollution control. Future development may include advanced training with higher spatial and temporal complexities to strengthen local capabilities.